Social Progress and the Dravidian “Race” in Tamil Social Thought - Collin Sibley (Genealogy, 2024)
In the closing decades of the 19th century, a wide range of Tamil authors and public speakers in colonial India became acutely interested in the notion of a Dravidian “race”. This conception of a Dravidian race, rooted in European racial and philological scholarship on the peoples of South India, became an important symbol of Tamil cultural, religious, and social autonomy in colonial and post-colonial Tamil thought, art, politics, and literature. European racial thought depicted Dravidians as a savage race that had been subjugated or displaced by the superior Aryan race in ancient Indic history. Using several key works of colonial scholarship, non-Brahmin Tamil authors reversed and reconfigured this idea to ground their own broad-reaching critiques of Brahmin political and social dominance, Brahmanical Hinduism, and Indian nationalism. Whereas European scholarship largely presented Dravidians as the inferiors of Aryans, non-Brahmin Tamil thinkers argued that the ancient, Dravidian identity of the Tamil people could stand alone without Aryan interference. This symbolic contrast between Dravidian (Tamil, non-Brahmin, South Indian) and Aryan (Sanskritic, Brahmin, North Indian) is a central component of 20th- and 21st-century Tamil public discourse on caste, gender, and cultural autonomy. Tamil authors, speakers, activists, and politicians used and continue to use the symbolic frame of Dravidian racial history to advocate for many different political, cultural, and social causes. While not all of these “Dravidian” discourses are meaningfully politically or socially progressive, the long history of Dravidian-centered, anti-Brahmanical discourse in Tamil South India has helped Tamil Nadu largely rebuff the advances of Hindu nationalist politics, which have become dominant in other cultural regions of present-day India. This piece presents a background on the emergence of the term “Dravidian” in socially critical Tamil thought, as well as its reversal and reconfiguration by Tamil social thinkers, orators, and activists in the 19th, 20th, and 21st centuries. The piece begins with a brief history of the terms “Dravidian” and “Aryan” in Western racial thought. The piece then charts the evolution of this discourse in Tamil public thought by discussing several important examples of Tamil social and political movements that incorporate the conceptual poles of “Dravidian” and “Aryan” into their own platforms.